Obstacles and Facilitating Factors in Decision-Making of Elderly Patients’ Living Will in the Chinese Context—A Literature Review - Zhang Y; Long W; Wang L; Yang L; Zhong J (Risk Management and Healthcare Policy, 2022)
Yanting Zhang,1,* Wenjia Long,2,* Ling Wang,3,* Liu Yang,4 Jun Zhong2,* 1Nursing Department, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 2Department of Gastrointestinal Surgery, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 3Department of Otolaryngology Head and Neck Surgery, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 4Department of Oncology Radiotherapy and Chemotherapy, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Zhong, Zhongnan Hospital of Wuhan University, Department of Gastrointestinal Surgery, Wuhan, Hubei, 430077, People’s Republic of China, Email 1881919@qq.comBackground: The living will provide patients at the end of life with the autonomy to choose medical care, so that the patients at the end of life can get dignified and die. In many countries such as Europe and the United States, this choice of people is guaranteed by the law. However, China is in its infancy in the field of living wills, lacking legal support, and the Chinese people have relatively low awareness of living wills and their acceptance is not optimism. China’s aging population is developing rapidly, and death education is getting more and more attention, and the popularity of living wills will increase further in the future.Objective: The aim of this review is to find out the obstacles and facilitating factors in the decision-making of elderly patients in the Chinese context, and to propose countermeasures.Methods: By searching for relevant literature in databases such as Cnki, Wanfang date, Weipu, Pubmed, Springer, Elsevier, etc., we can understand the connotation of the living wills of elderly patients at home and abroad and the obstacles and promotion factors that affect the signing of the living wills of elderly patients in China.Results: In the Chinese context, obstacles and facilitating factors in the decision-making of elderly patients’ living will can be summarized at the individual, social, and national levels. The obstacles are: low quality of hospice care, social ethics, and lack of legal support. Facilitating factors include: meeting people’s psychological expectations, respecting personal autonomy, conducive to the mental health of dying patients and their caregivers, and patients’ willingness to accept living will.Conclusion: Need to determine relevant specific influencing factors, formulate intervention measures, and promote the development of death education in China to ensure gradual progress.Keywords: elderly, living will, advance medical directive, pre-existing death, obstacle, promotion, summary